2007
DOI: 10.3171/foc.2007.22.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of the Dynesys dynamic neutralization system: 1-year preliminary results

Abstract: Object In this study the authors present the preliminary clinical outcomes of dynamic stabilization with the Dynesys spinal system as part of a multicenter randomized prospective Food and Drug Administration (FDA) investigational device exemption (IDE) clinical trial. Methods This study included 101 patients from six IDE sites (no participants were omitted from the analysis) who underwent dynamic stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 30 publications
3
73
0
Order By: Relevance
“…These results are in agreement with Welch et al (32), that reported the same level of improvements in a larger population (101 patients) but after only 1-year follow-up of the Dynesys system, with Stoll et al (33), where a consecutive series of 83 patients was studied for different follow-up times (range, 11.2-79.1 months), and with the recently published work of Cienciala et al (34) where 102 patients were followed for a 3-year period.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with Welch et al (32), that reported the same level of improvements in a larger population (101 patients) but after only 1-year follow-up of the Dynesys system, with Stoll et al (33), where a consecutive series of 83 patients was studied for different follow-up times (range, 11.2-79.1 months), and with the recently published work of Cienciala et al (34) where 102 patients were followed for a 3-year period.…”
Section: Discussionsupporting
confidence: 94%
“…Clinical data for posterior pedicle screw-based dynamic stabilization show mixed outcomes ranging from comparable to fusion [10,11,[13][14][15]42] to worse than fusion [16,17], which could be attributed to the different clinical indications. Obviously, the latter (e.g., disc degeneration, spinal stenosis with or without degenerative spondylolisthesis, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In clinical use since 1994 [9], Dynesys has shown mixed results, strongly dependent on the clinical indication [10][11][12][13][14][15]. Apparently, a complication attributed to its inadequate stabilization in the transversal plane may be the disability to eliminate radicular pain [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Welch et al [25] in a multicentric study reported 101 patients with lumbar spinal stenosis and degenerative spondylolisthesis with a 12-month follow-up. Fifteen of 101 patients required 18 reinterventions at the time of the 1-year follow-up evaluation, from these, 11% underwent 13 procedures related to the spine or the index surgery.…”
Section: Discussionmentioning
confidence: 99%